Game Monster Hunter sebagai Inspirasi dalam Karya Drawing Menggunakan Teknik Cross Hatching - Ottosay Pratama; Nelson Tarigan; Raden Burhan Surya Nata Diningrat (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This work was created out of the author's interest in the world of video games and realized in the form of graphic art. In this video game, the author found interesting aspects of the Monster Hunter game, starting from its ecosystem, system, and the excitement of playing it. Until the point where the author encounters bosses in the game called elder dragons, including Gore Magala, Shagaru Magala, and Valstrax. This research aims to bring the world of the game to life as a work of art. In this research, the author created 15 artworks depicting monster forms, monster hunts, and tasks that monster hunters must undertake. In creating this work, the author used a pen with black and white ink, employing the cross-hatching technique. This technique helps the author create a dynamic impression, contrast, balance, and volume, and also makes it easier for the author to add depth to the shading in the created works. The result of this research produced 15 works with titles taken from several video game references and some tasks taken from monster hunters.